THE EFFECT OF DISTRIBUTION OF AZOLLA JUICE IN DRINKING WATER ON CUTTING OF BROILER CARCASS - D. P. I., Pranata; Siti, N. W.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aimed to determine the effect of giving azolla juice to drinking water on cuts of broiler chicken carcass. This research was conducted in Yangapi Village, Tembuku District, Bangli Regency, Bali for 5 weeks from preparation to completion. The design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, thus there were 16 experimental units. Each experimental unit contained 4 broilers aged 7 days and 64 broilers were used. The treatments given were broilers given drinking water without azolla juice (P0), broilers given drinking water with 2% azolla juice (P1), broilers given drinking water with 4% azolla juice (P2), and broilers given drinking water with 6% essence of azolla juice (P3). The variables observed were the percentage of carcass cuts (breast, upper thigh, lower thigh, back and wings). The results showed that the percentage of broiler wings and back that received treatment P1, P2 and P3 decreased compared to treatment P0, but was not statistically significantly different (P> 0.05). Meanwhile, the percentage of chest, upper thighs, and lower thighs was higher than the P0 treatment but statistically not significantly different (P>0.05). From the result of the study it can be concluded giving azolla extract in drinking water at a rate of 2%, 4%, 6% in broiler chickens has not beet able to increase the cut of carcasses.